Analisis Determinan Waktu Pengungkapan Status Diri Odha Terhadap Pasangan Di Kabupaten Sikka Tahun 2015 - Maria Kornelia R. Kuwa (Jurnal Keperawatan Florence Nightingale, 2019)
The spread of HIV AIDS in Indonesia continues to increase every year. HIV positive people in Indonesia until the 3rd trimester of 2012 reached a cumulative number of 86,762 cases. This study aimed to analyze the Time of Disclosure of the Status of Self-Individuals of PLHAs to couples in Sikka District. The type of research was an explanatory research with the approach of the cross sectional approach. The sample was 160 respondents. The data were analyzed using univariate, bivariate and multivariate chi square statistical test. The results of this study indicated that the time of disclosure of HIV status of respondents to the couple most of the respondents revealed faster by 53.1%. The fastest time was 1 (one) day and the longest was 1,825 days (5 years) with the average time of disclosure to the couple was 218.46 days. Bivariate variables related to disclosure time were age (p = 0,010), marital status (p = 0,006), participation of peer support group (p = 0,002), and counselor support (p = 0,000, while unrelated variables were type (P = 0,830) The result of multivariate analysis stated that the most influential factor was support from counselor (OR / Exp (B) = 3,723) that the respondent got support from counselors has a 3-times greater tendency to more quickly disclose HIV status to their partners than those who do not get support from counselors.This study recommends the need for increasing the health promotion efforts related to the HIV epidemic rate control, particularly regarding the timing of HIV status disclosure to the couples in an effort to reduce the risk of HIV transmission to partners from sexual pathways through safe sexual behavior.